If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + -7g = -24 Combine like terms: 2g + -7g = -5g -5g = -24 Solving -5g = -24 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by '-5'. g = 4.8 Simplifying g = 4.8
| 6x+39=14x-66 | | -2(x-4)=12 | | 7x+3y=6x+5y | | -2(-2-4)=12 | | 6=4d-10 | | Y-4=7x(x-3) | | 5+5q=6+4q | | 6(2+-5)+5t=60-1 | | 11-j=2 | | 5+6=9+3 | | 18-13=m | | 2a+4b=30 | | 1.25=0.75r | | -.2t^2-14t=0 | | 25=x+1+2x+3 | | a-10=10 | | 22x-44y= | | 1y+0x=4 | | 0.2x+7.3=6.4 | | (2x+-3)*x=54 | | 9(0)+7x=63 | | 8.65x-6.5=-34.04+13.75x | | 16a=80 | | 3x^3+11x^2-15x+16*3x+2= | | -2=3f-5 | | 4x+2y=6x+12 | | 9(0)+7x^2=63 | | 5(y-6)-16=-11 | | 35*7=(X*7)+(5*7) | | 3=12+k | | 8(8)(-7)(-6)= | | 2a+ab=18 |